RNA Sequencing Reveals Dynamic Carbohydrate Metabolism and Phytohormone Signaling Accompanying Post-mowing Regeneration of Forage Winter Wheat (Triticum aestivum L.) - Cui, Guibin; Zhao, Mei; Tan, Hongbin; Wang, Zhulin; Meng, Min; Sun, Fengli; Zhang, Chao; Xi, Yajun (Frontiers in Plant Science, 2021)
Winter wheat (Triticum aestivum L.) is used as fresh green winter forage worldwide, and its ability to regenerate after mowing determines whether it can be used for forage production; however, the molecular mechanism of regeneration is poorly understood. This study identified long-chain coding and non-coding RNAs in the wheat cultivar ‘XN9106’, which is cultivated for forage and grain production separately in winter and summer, and analyzed their function during post-mowing regeneration. The results showed that the degradation of carbohydrate plays an important role in regeneration, as demonstrated by decreased carbohydrate content. The increased gene expression and enzyme activity of β-amylase, β-fructofuranosidase, sucrose synthase, sucrose-phosphate synthase, trehalose-6-phosphate synthase, and trehalose-6-phosphate phosphatase in mowed seedlings indicates regeneration is fueled by degraded carbohydrates that provide energy and carbon skeletons for the Krebs cycle and amino acid synthesis. The decreased auxin content relieved the inhibition of cytokinin synthesis, that controls the transition from cell division to cell expansion and stimulates cell expansion and differentiation during the cell expansion phase, and eventually accelerate post-mowing regeneration of seedlings. Additionally, 39 differentially expressed lncRNAs were shown to participate in the regulation of the expression of key genes involved in carbohydrate metabolism and hormone signal transduction. This study demonstrated the molecular responses of long-chain coding and non-coding RNAs during post-mowing regeneration of winter wheat and revealed key mRNAs and lncRNAs involved during regeneration, providing valuable information for genetic improvement of forage wheat.